2022
DOI: 10.3390/en15134815
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies of the Effect of Air Filter Pressure Drop on the Composition and Emission Changes of a Compression Ignition Internal Combustion Engine

Abstract: This paper presents an experimental evaluation of the effect of air filter pressure drop on the composition of exhaust gases and the operating parameters of a modern internal combustion Diesel engine. A literature analysis of the methods of reducing the emission of toxic components of exhaust gases from SI engines was conducted. It has been shown that the air filter pressure drop, increasing during the engine operation, causes a significant decrease in power output and an increase in fuel consumption, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 76 publications
(93 reference statements)
0
7
0
Order By: Relevance
“…The control of the air heater was carried out via dSPACE. An air filter mounted in front of a supercharger has a significant effect on the performance of the intake system and causes a certain pressure drop [41,42]. The air filter also has a considerable effect on the flow resistance [43,44].…”
Section: Methodology 21 Experimental Setupmentioning
confidence: 99%
“…The control of the air heater was carried out via dSPACE. An air filter mounted in front of a supercharger has a significant effect on the performance of the intake system and causes a certain pressure drop [41,42]. The air filter also has a considerable effect on the flow resistance [43,44].…”
Section: Methodology 21 Experimental Setupmentioning
confidence: 99%
“…In these works [183,332,333], the authors have repeatedly shown that the shape of the combustion chamber in RCCI engines is crucial for forming harmful chemical compounds in exhaust gases. The air-fuel mixture's degree of swirling changes, making it possible to burn the fuel [334] completely. After installing the gas fueling system, engine operation should be optimized using an engine dynamometer and an exhaust pollution measurement system (which is not always accessible).…”
Section: Discrepancies In Hcng Datamentioning
confidence: 99%
“…The adverse effects of CO 2 emissions on both environmental sustainability and public health have been thoroughly documented in various studies, emphasizing the urgent need to substantially reduce these emissions [5]. This urgency is driven primarily by two reasons: First, the global commitment to mitigate climate change impacts, and second, the understanding that reducing CO 2 emissions, through measures like decreasing fuel consumption, contributes to conserving our limited fossil fuel reserves [6,7]. However, despite the adoption of various strategies encompassing technological innovations [8] and policy regulations to curb CO 2 emissions, the increasing number of gasoline vehicles worldwide still presents a significant challenge to CO 2 emission reduction efforts [9][10][11][12], emphasizing the importance of accurate vehicular CO 2 emission estimation.…”
Section: Introductionmentioning
confidence: 99%